Tunable colloidal quantum dot distributed feedback lasers integrated on a continuously chirped surface grating. Issue 48 (5th December 2018) - Jung, Hyunho; Han, Changhyun; Kim, Hanbit; Cho, Kyung-Sang; Roh, Young-Geun; Park, Yeonsang; Jeon, Heonsu
Abstract : Continuously tunable colloidal quantum dot distributed feedback lasers are fabricated on a chirped surface grating generated by a laser interference lithography apparatus equipped with a cylindrical Lloyd's mirror. Abstract : We report a colloidal quantum dot (CQD) distributed feedback (DFB) laser structure containing a chirped grating. The device exhibits single-mode DFB lasing, of which the wavelength is spatially dispersed in a single chip. A period-chirped surface grating is fabricated using a modified Lloyd-type laser interference lithography setup, where a flat Lloyd's mirror is replaced with a concave one. A dense red-emitting CdSe/CdS/ZnS CQD film is prepared on a temporary substrate by spin-coating, which is subsequently released and wet-transferred onto a period-chirped quartz surface grating. Upon optical excitation, the fabricated DFB laser device lases in a single mode at a laser threshold of ∼400 μJ cm −2, with its lasing wavelength shifted linearly (in proportion to the grating pitch) along the chirp direction from 613.4 nm to 623.2 nm over a distance of ∼5.6 mm.